Comparisons of microbiota-generated metabolites in patients with young and elderly acute coronary syndrome - Mustafa Begenc Tascanov; Zulkif Tanriverdi; Fatih Gungoren; Feyzullah Besli; Musluhittin Emre Erkus; Ismail Koyuncu; Ataman Gonel; Gulsen Genc Tapar (Anatolian Journal of Cardiology, 2020)
Objective: Acute coronary syndrome (ACS) is a leading cause of death worldwide. There is great interest in defining the risk factors and underlying mechanisms of ACS among young people. The microbiota and its metabolites have recently become a popular research topic, yet there is still no study that investigated microbiota-generated metabolites as a possible risk factor in young patients with ACS. In this study, we aimed to investigate the relationship between microbiota-generated metabolites and ACS in young people. Methods: This study included 44 young patients with ACS (<50 years of age), 39 elderly patients with ACS, and 44 patients with normal coronary arteries. Inflammatory parameters and serum trimethylamine N-oxide (TMAO) and choline levels were measured in all patients. Results: Young patients with ACS had significantly higher levels of TMAO and choline compared to the control and elderly ACS groups. Also, elderly patients with ACS had a significantly higher level of TMAO than the control group. Linear regression analysis was performed to determine the independent predictors of TMAO. Two regression models were involved. The first model included young ACS and control groups, while the second model included young and elderly ACS groups. In the first model, we found that young ACS (ß=0.399, p=0.004) and smoking ACS (ß=0.211, p=0.046) were significantly associated with TMAO level. In the second model, young ACS was significantly associated with TMAO level (ß=0.230, p=0.035). Conclusion: In this study, we have shown that young ACS was significantly associated with increased TMAO level.